Caring for the community: An academically based community service course in LIS. (March 2023) - Lee, Kung Jin; Kim, YooJung; Roldan, Wendy; Lee, Jin Ha; Yip, Jason C.
The field of Library and Information Science (LIS) has historically struggled to connect theory and practice in its graduate education, specifically when it comes to building partnerships with diverse stakeholders in public library communities. One possible technique for bridging the gap of stakeholder experiences is academically based community service (ABCS) courses. ABCS courses attempt to directly focus on research-practitioner partnerships to solve real-world problems by involving the community to democratically co-design the curriculum. In this paper, we present a reflective case study of an ABCS course on integrating participatory design methods to co-design new digital learning activities for youth in an urban public library. By conducting 10 co-design sessions and 26 semi-structured interviews, we examined a partnership between a university and a library, and how this ABCS course impacted different stakeholder participation. Our findings highlight how ABCS courses require systematic structural endeavors from higher education and care between all stakeholders within a library setting. This work contributes to a growing body of work that calls for more courses in LIS education with greater civic and democratic engagement between graduate students, university partners, and library stakeholders.